A de facto Asian-currency unit bloc in East Asia: It has been there but we did not look for It - Eric Girardin (Asian Development Bank Institute (ADBI), 2011)
Pegging in a coordinated way to a regional basket currency is considered by many as optimal for east-Asian countries. By contrast, according to existing empirical studies, these countries have most often relied on noncooperative United States dollar or G3 pegs. We show for the first time that by the late 1990s, with some reversals, a majority of east-Asian countries had already moved, de facto, away from the dollar peg and started targeting a basket, including east-Asian currencies (an Asian Currency Unit). Common-shock or market-based interpretations of such moves are ruled out since we document that, with few exceptions, countries in the region have in reality stuck to fixed exchange rates. We obtain such results using a Markov-switching estimation benchmarked against Bai-Perron structural break tests for the synthesis model of Frankel and Wei (2007), which augments the inference about currency weights in a basket with the weight on exchange-market pressure. In order to measure the latter, the forward positions of central banks in the foreign exchange market are taken into account.
Keywords: F31; F41; 330; Wechselkurssystem; Währungskorb; Fester Wechselkurs; Währungspolitik; Wirkungsanalyse; Asien